Characterization of a metallo-protease produced in solid state fermentation by a newly isolated Bacillus strain - Saxena, Rajshree; Singh, Rajni (Acta Biologica Szegediensis, 2011)
A metalloprotease was characterised from a newly isolated Bacillus strain. The enzyme activity was stimulated by mono- and divalent metal ions at 5 and 10 mM concentration and inhibited by EDTA, DTT and B ME (95, 90 and 80%, respectively) at 10 mM concentration. The enzyme inhibition caused by 10 mM EDTA was restored by 45-47% with 5 and 10 mM NaCl. These characteristics established the enzyme as a metalloprotease. Different agroindustrial substrates were used for economic production of the metalloprotease, among which rice bran was selected as best providing z1000 U protease /g of substrate in 72 h with 20% inoculum and 1:3 moisture content (w/v). The enzyme was thermostable (30-50oC) with maximum activity at 60°C. It also exhibited a broad pH activity range (6-9) with a maximum at pH 8.